2008
DOI: 10.1007/978-3-540-88594-8_8
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Framework for the Declarative Debugging of Datalog Programs

Abstract: Abstract. The logic programming language Datalog has been extensively researched as a query language for deductive databases. Although similar to Prolog, the Datalog operational mechanisms are more intricate, leading to computations quite hard to debug by traditional approaches. In this paper, we present a theoretical framework for debugging Datalog programs based on the ideas of declarative debugging. In our setting, a debugging session starts when the user detects an unexpected answer for some query, and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…VIDEAS has been implemented on top of the Eclipse platform. 5 In particular, technologies provided by the Eclipse Modeling Framework (EMF) 6 and the Graphical Modeling Framework (GMF) 7 projects have been used. The meta-model representing the ER diagram modelling language has been created using the Ecore modelling language which is specified within the EMF project.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VIDEAS has been implemented on top of the Eclipse platform. 5 In particular, technologies provided by the Eclipse Modeling Framework (EMF) 6 and the Graphical Modeling Framework (GMF) 7 projects have been used. The meta-model representing the ER diagram modelling language has been created using the Ecore modelling language which is specified within the EMF project.…”
Section: Methodsmentioning
confidence: 99%
“…However, practice has shown that the development of answer-set programs is not always straightforward and that programs are, as all human-made artifacts, prone to errors. In fact, debugging in ASP is currently a quite active research field [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Some tools as [2,13] allow the user to trace and analyze the stored SQL procedures and user defined functions, but they are of little help when debugging systems of correlated views. Declarative Debugging, also known as algorithmic debugging, is a technique applied successfully in (constraint) logic programming [16], functional programming [12], functional-logic programming [5], and in deductive database languages [3]. The technique can be described as a general debugging schema [11] which starts when an initial error symptom is detected by the user, which in our case corresponds to an unexpected result produced by a view.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike existing work that focuses on obtaining only one provenance path, the novelty of this work consists in obtaining all provenance paths to a ground query. This problem is relevant in many practical applications such as explanation [9], abduction [13], debugging [4] and notably, defeasible reasoning. In [11], the authors have stumbled upon this problem as query answering in defeasible reasoning with existential rules became unsound due to provenance path loss (not all provenance paths could be extracted).…”
Section: Introductionmentioning
confidence: 99%
“…Extracting the provenance paths for the query q using backward chaining [4] is not possible as it is infinite. To extract provenance paths using forward chaining the state of the art uses a chase graph [6] (also called derivation tree [1]).…”
Section: Introductionmentioning
confidence: 99%